UNDERSTANDING LITERACY CONSTRAINTS IN ELEMENTARY CLASSROOMS; EVIDENCE FROM THE KAMPUS MENGAJAR INITIATIVE - Diyah Nur Hidayati; Ninda Beny Asfuri; Fattah Wahyu Kusumo; Rafifah Putri Nur Aini (PEDAGOGIK : JURNAL PENDIDIKAN, 2025)
This study explores the literary skills of elementary school students in Surakarta, that focusing on factors influencing their development. Employing a descriptive qualitative method, the study investigates the experiences and perspectives of university students participating in the Kampus Mengajar program in Soloraya, spanning the Kampus Mengajar 3 to Kampus Mengajar 7 over two years with a total of 21 respondents. The data was collected through an open-ended survey using Google Forms, supplemented by field supervisor lecturer observations and analyses of students' reports. The study's findings show four major issues that students with reading difficulties face: a lack of parental education prioritization, poor student motivation and enthusiasm, and the presence of specific educational requirements. Furthermore, teachers use a variety of tactics to address these reading issues, such as reading aloud, playing interactive games, creating specific educational modules, and offering tailored reading support. In addition, parental attitudes about their children's literacy challenges are marked by denial of their children's literacy problems and participation in home-based reading activities. The study also identifies dyslexia indicators and emphasizes the importance of inclusive education solutions for kids who struggle with reading.